A interface História da Ciência e ensino de Ciências em documentos curriculares da educação brasileira (de 1960 aos tempos atuais) - Leal, Raiza Caroline de Oliveira (2024)
What is the objective of teaching science? Possibly this is the leading question to be problematized in the present work. The historical outline of this research discloses different educational objectives in the area – instrumental training of individuals, technical-professional and citizen-critical. A look at the main curricular documents of basic education allows us to analyze the political-economic outlook of Brazilian context and how different historiographical perspectives of the History of Science are placed to meet educational objectives. Would this be the role of this field of knowledge in the interface with teaching? In this research, we advocate for the humanization of scientific knowledge in education and approaches that promote reflections regarding the legitimization of this set of knowledge as a social pact – a space for power struggle, interests and validation. Therefore, the present research proposes, through documentary analysis and literary review, to understand what are the trends in the vision of science and History of Science that permeate the head guiding documents in the area of natural sciences in the last stage of basic education, the high school